Enhancing Molecular Geometry Understanding through 3D Visualization-Assisted Intertextual based Learning in Undergraduate Chemistry Students - Ajie, Adinda Melinda Ceria; Wiji, Wiji; Mulyani, Sri; Widhiyanti, Tuszie (Jurnal Pendidikan MIPA, 2024)
Intertextuality refers to the process of understanding a context by exploring and connecting relationships between different texts or representations. In chemistry education, intertextuality serves as a communication bridge that links the three levels of chemical representation: macroscopic, submicroscopic, and symbolic. This study aims to enhance students' understanding of Molecular Geometry Concepts through Intertextual-based Learning with 3D- visualization. The research employed a quantitative approach with a one-group pretest-posttest design. Participants were selected using purposive sampling from undergraduate chemistry education students. The study involved 26 first-year students majoring in chemistry education who were taking a general chemistry course. Data were collected using student worksheets and pretest-posttest assessments. The data analysis included t-paired test for parametric statistic and evaluating student responses related to learning outcomes. Analysis of the t-paired test results shows that there is a significant difference in the pretest and posttest scores with a significance value of (p> α0.05). The most influenced concept indicator in this study was the concept of molecular geometry types with an increase of 57% in students’ correct answers.       Keywords: student’s understanding, molecular geometry, intertextual based learning, 3d visualization, undergraduate students. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1468-1479